THE EFFECTIVENESS OF USING FAIRY TALES MAZE FOR TEACHING READING COMPREHENSION TO THE EIGHTH GRADE STUDENTS OF JUNIOR HIGH SCHOOL (RETAIN, 2014)
THE EFFECTIVENESS OF USING FAIRY TALES MAZE FOR TEACHING READING COMPREHENSION TO THE EIGHTH GRADE STUDENTS OF JUNIOR HIGH SCHOOL Lila Setyaningsih 102084201 English Education Department, Faculty of Language and Art, Surabaya State University,e-mail lyla_setyaningsih@yahoo.co.id Dosen Pembimbing Him’mawan Adi Nugroho S.pd.,M.Pd. English Education Department, Faculty of Language and Art, Surabaya State University,e-mail himmawan_95@yahoo.co.id Abstrak Dalam mempelajari bahasa ada beberapa aspek bahasa yang umumnya dipelajari oleh siswa, yaitu; mendengar,berbicara,membaca dan menulis. Membaca menjadi salah satu aspek terpenting yang harus dipelajari oleh siswa, karena membaca adalah salah satu kunci sukses dalam belajar (Butler, dkk. 2010). Ada berbagai cara yang dapat diterapkan oleh guru untuk meningkatkan kemampuan pemahaman bacaan pada siswa. Beberapa strategi yang dapat diterapkan oleh guru diantaranya adalah 1)mampu membuat siswa menebak apa yang akan terjadi pada bacaan dengan melihat judul bacaan tersebut, 2) mampu mengarahkan siswa untuk bertanya pada dirinya sendiri tentang apa yang harus dia cari dalam bacaan tersebut, 3) mampu mengarahkan siswa untuk mampu menerapkan apa yang telah dia ketahui tentang bacaan pada saat membaca, 4)mampu membuat siswa membayangkan isi dari bacaan saat mereka membaca. Untuk menerapkan strategi tersebut guru membutuhkan Fairy Tales maze sebagai materi untuk meningkatkan kemampuan pemahaman siswa. Fairy tales maze sendiri adalah cerita imajinatif tentang peri, raksaa, kerajaan, dsb yang disajikan dalam bentuk rumpang. Teks rumpang yang disediakan akan berbeda dengan teks rumpang biasa karena pada hampir setiap kata ke tujuh setelah kalimat pertama digantikan dengan 3 kata yaitu 2 kata yang salah dan 1 kata sebagai jawaban yang benar (Milone, 2006). Untuk mengetahui seberapa efektif Fairy tales maze daam meningkatkan kemampuan pemahaman pada siswa maka dilakukan penelitian kepada siswa SMPN 1 Tarik sebagai subjek, dengan VIII C sebagai experimental grup dan VIII D sebagai kontrol grup. Try-out dilakukan kepada siswa kelas VIII H untuk mengetahui validitas dan realibilitas dari tes yang digunakan dalam penelitian ini, dan hasil menunjukkan bahwa tes yang digunakan valid dan reliabel. Pre-tes dilaksanakan sebelum treatmen dan post-test dilakukan setelah treatmen. Berdasarkan analisis dari SPSS yang membandingkan antara nilai pre-test dan post test kedua grup ini menunjukkan nilai rata-rata 46,30 dengan standard deviasi 9,933 untuk kontrol grup menurut independent sample T-test dari SPSS. Sedangkan untuk experimental grup nilai rata-rata grup adalah 51,81 dengan standar deviasi 10,702, dan nilai p untuk keduanya adalah 0.35 atau dengan kata lain ini lebih tinggi dari 0,05. Menurut Pallant (2010) nilai p lebih besar dari 0,05 menunjukkan tidak ada perbedaan yang signifikan untuk kedua grup yang dibandingkan. Dengan kata lain dapat disimpulkan bahwa Fairy tales maze tidak efektif untuk meningkatkan kemampuan pemahaman bacaan pada anak. Kata kunci: Fairy tales maze, pemahaman membaca, teks narative, mengajar membaca anak kelas VIII Abstract This thesis written in order to implement Fairy Tales Maze as a reading material for teaching reading comprehension to the junior high school students. According to Butler et al, (2010) stated that there is strong relation between reading ability and academic success. However, there are some strategies must be activate to drive students into good comprehension such as; predicting, questioning, connecting and visualizing. As stated by Iwai (2007) Comprehension can be activated through activate background knowledge. This study aimed to find out the effectiveness of Fairy tales maze for teaching reading comprehension to the eighth grade students of junior high school. This study was conducted in SMPN 1 Tarik. In addition, since this study is experimental there are two subjects in this study; they are the students of VIII C and VIII D as the experimental and control group. To collect the data the instrument used by the researcher is test (Try-out, Pre-test and Post-test). After provided Fairy tales maze for the students, the test was conducted in form of multiple choice question in order to measure students’ comprehension. The researcher analyzed the result by using Independent sample T-test and Paired sample T-test on SPSS. The result showed that the mean value of control group’s score is 46,30 with SD = 9,933. However, the mean value of the experimental group is 51,81 with SD = 10,702, and the p value of this analysis is 0,35. The p value was not less than 0.05 or higher than 0.05 means that there is no significant difference between these two groups. According to the result, the Fairy Tales Maze is ineffective for teaching reading comprehension to the eighth grade students of junior high school. Since the result showed that there is no significant difference on students’ comprehension between those who are taught using fairy tales maze and those who are taught using conventional teaching material. Keywords: Fairy tales maze, Narrative Text, Reading Material, Reading Comprehension, Teaching Reading Eighth grader students INTRODUCTION Since English is an International language, it is important for everyone to be able to use English as a foreign or second language. In Indonesia as an EFL countries English has been taught since children are in the kindergarten. It has been taught on varieties of skills such as listening, speaking, reading and writing. As stated by Finochiaro (1975:10) language learners should learn a real communication situation and teacher should give insight function of various language item skills in listening, speaking, reading and writing activities. Those four skills have each role in students’ development of knowledge and learning ability. However, reading is one of the skills that crucial to be mastered. As stated by (Butler, et al. 2010) almost more than a half century research has constituted a correlation between academic success and those who learned reading early and easily. Otherwise, learners who are lack of knowledge on reading will get difficulties on understanding the information on text when they are reading. According to (Rice, 2009) stated that reading is the process of interaction between reader and a text to construct meaning (comprehension). Some students argue that reading skill is easier to be mastered than the other skill. However, the condition happen in a real life is different. There are a lot of students who still get difficulties in comprehending the text. They who lack in comprehending the text usually focus more on word accuracy rather than on the message of the text. Many students from different level are still unable to comprehend text, especially English text. According to (Cain and Oakhill, 1999; Nation et al., 2005) cited by NSW Department of Education and Training (2010) stated that they who tend to read superficially are less likely to participate in constructive processes and unsure when to apply their knowledge during reading. Most students thought that successful reader is those who read fluently and able to complete the task, but some of them ignore the sentence that they use to complete the task. When completing the short answer question most students tend to copy the sentence directly from the text rather than construct their own sentence, unless students of junior high school. This habit should be abolished because it shows that students do not understand well the text that they read. That is why teacher should have a goal to minimize reading difficulties and maximize comprehension when teaching reading. As a consequent, based on the problems above the researcher try to offer a solution for teaching reading narrative, that is by using Fairytales maze. In addition, Fairytales maze is a combination between fairytales and story maze or maze passage which is used as a material for teaching reading narrative text. As stated by Milone (2006) maze passage is a text for reading which after the first sentence in every seventh word is replace with two distracter and one fix answer. Since the subjects of the study or the students are EFL learner, the researcher modifies the maze. The maze passage used by the researcher replaced in mostly after the seventh word because researcher should consider on students’ ability on understanding the text. Story maze is good because it helps students to activate their thinking ability on choosing the diction, because, while reading the text students also need to fill the blank on the text with appropriate vocabulary in order to complete the story. Besides, according to the related study by Butler et al (2010) stated that teaching students using multiple strategies can increase students’ comprehension. In this study the researcher use 4 strategies such as predicting, questioning, connecting and visualizing. That is why the researcher use Fairy tales maze to activate those strategies. Even though, students may never read the text of Fairytales that provided by the teacher, but they may have watched the film. Consequently, while reading they will comprehend the text well by connecting and visualizing the text they read with their experience. A related study by Iwai (2007) stated that a good comprehension will be build through activate background of knowledge. It means that readers or students will be able to make connection between their background knowledge (watch film) with their new knowledge (read text). Besides, most students will satisfy to read the text because most of children interest in reading fairy tale story, at least it has vanished students reluctance on reading. As stated by (Iwai, 2007) students’ motivation on reading a text is the start of comprehension development. It means that when students are reluctant to read the text, then, it will be so hard to make them comprehend it. Fairy tales maze provided for increasing students’ comprehension of narrative because fairy tales have language features and structure as narrative. As stated by (Iwai, 2007) when reader know the structure of the text, they will easily read the text because they already know what kind of information that must be found. As an example when readers already know the structure of Narrative text, they will easy to find out the problem of the story and the resolution. Besides, after read and completed the Fairy tales maze students have to answer some multiple questions related with the text they read in order to drive them into good comprehension. As stated by Butler et al (2010) in their study about comprehension instruction found that question answering can increase students’ comprehension. Therefore, giving Fairytales maze as a teaching material for junior high students will automatically activate their background knowledge toward the text given. Consequently, their ability in comprehending the text will also increase. Deal with the problem above the researcher conducted a study in order to find out the differences between students who are taught using fairy tales maze and those who are taught without using fairy tales maze. Consequently the problem statement appear as; is there any significant differences between students who are taught using fairy tales maze and those who are taught without using fairy tales maze? The researcher use fairy tales maze as an alternative material for teaching reading comprehension to the eighth grade students in SMPN 1 Tarik. METHOD The design study of this research is experimental quantitative study. Therefore, there are two groups which are used as the subject of this study, they are; VIII C as the experimental group and VIII D as the control group. These two groups were taken from the population that is the eighth grade students of SMPN 1 Tarik. Both groups were given pre-test to know their reading ability. Then, the experimental group was given treatment by using fairy tales maze as a reading material for teaching reading comprehension. Therefore, the control group was taught by using conventional material without special treatment. For the last, both groups were given post-test to measure whether or not the fairy tales maze can be effective for teaching reading comprehension through narrative for eighth grade students. Since it is experimental study, there are two variables namely; independent variable and dependent variable. The independent variable of this study is the subject of the study, while the dependent variable is the result score of both groups. The instrument use to collect the data is test. The researcher conducted three times test that are; try-out, pre-test, and post-test. Try-out test was conducted to the group which are not belongs to the experimental or control group. Try-out test conducted to measure the validity and the reliability of the test. For analyzing the reliability of the test the researcher uses SPSS analysis and also Kurdher Richardson formula (KR-21). The test instrument use by the researcher consist of 50 question related to narrative. The test item was constructed based on the objective of the study (kurikulum KTSP 2006) such as; identifying the topic, main idea of the text, generic structure, contextual pronoun, certain vocabulary on the text, inferring certain paragraph and identifying specific information from the text. In addition, to analyze the data the researcher use independent sample and paired sample analysis on SPSS. Firstly, the researcher tabulating the result score on excel then convert it into SPSS. Next, look at the p value (-sig 2 tailed) when the value is less than .05 means that there is significant difference on the groups, while if it is higher than .05 means that there is no significant difference between groups. After looking at the p value, calculate the eta-square by using these formulas (pallant, 2010) Eta-square for Independent sample T-test = Eta-square for paired sample T-test = After calculating the effect size, then comparing the result of effect size with the scale of effect size value. According to Cohen (1988, pp.284-7) cited by Pallant (2010) The guidelines for interpreting the value of eta square are: (.01=small effect – .06=moderate effect – .14=large effect). FINDING AND DISCUSSION After had been administered pre-test to the control and experimental group in two different sections, the researcher got the result score. This following result is the answer of the research question. If the result of this study about the effectiveness of Fairy tales maze for teaching reading comprehension shows that Fairy tales maze is effective for teaching reading comprehension, means that this result accepted Alternative Hypothesis (Ha) and rejected the Null hypothesis. However, if the result of this study shows that there is no significant difference, means that this result accepted the Null Hypothesis (Ho) and rejected the Alternative Hypothesis. For answering the problem statement the researcher compared the results score between control and experimental group. Pre-test score was compared to find the difference between these groups before treatment applied. Post-test score was compared to find the differences between these groups after the treatment and to identify whether Fairy tales maze effective or not. The following discussion is the presentation analysis of this study. Pre-test was conducted to 32 students in experimental group and 33 students in control group. The table bellow shows the result analysis of students’ pre-test score using independent sample T-test on SPSS. The result shows that both groups are equal. Table 4.1: The result analysis of Pre-test using Independent sample T-test by using SPSS As presented in the table above that there is no significant difference between these groups with (M=42.30 and SD= 7.618) for control group. While for the experimental group the results are (M= 45.31 and SD= 7.249); t=1.631 and 1.632 p=0.108 two tailed. The difference of t value between these groups is caused by the difference amount of subject in these groups. The magnitude of the differences in the means (means difference = 3.009, 95% CI = -.676 to 6.695). However, the eta square of this analysis shows 0.04, it means that the intervention was small. Based on the p value = .108 it is higher than .05 means that there is no significant difference. As stated by Pallant (2010:241) if the p value higher than .05 means that the equal variance assumed. The second data presented is about the comparison between control and experimental group in Pre and Post test. This analysis was done in order to find the improvement of the group after the treatment applied. Table 4.2: the analysis of Pre- and Post-test Paired Samples Statistics Mean N Std. Deviation Std. Error Mean Pair 1 PreTest 43.78 65 7.534 .935 PostTest 49.02 65 10.619 1.317 Table 4.3: The SPSS table of comparison students’ pre-test and post-test score Paired Samples Test Paired Analysis T Df Sig. (2-tailed) Mean Std. Deviation Std. Error Mean 95% Confidence Interval of the Difference Lower Upper Pair 1 PreTest - PostTest -5.231 12.014 1.490 -8.208 -2.254 -3.510 64 .001 As been shown above, the researcher compared the result score between these groups by using Paired sample T-test. It is use to compare students’ pre-test score and post-test score. The researcher uses the result of this comparison to know the improvement of students’ reading ability after teaching learning process. Moreover, the result shows that there is significant differences on students’ score between pre-test and post-test with p value=.001 -2tailed, it is less than .05. Also the differences on mean value (table 4.2) (pre-test = 43,78 and post-test = 49,02) indicate that there are improvement on students’ score. The calculation of eta-squared = 0.16, it shows high intervention. After comparing students’ score between pre-test and post-test to know the improvement of students’ reading comprehension the researcher compares students’ post-test score. This comparison is used to know the differences between students who are taught by using fairy tales maze and those who are taught without using fairy tales maze. The next analysis also used to find out the answer of problem statement in this study. Same as the first comparison the researcher used independent sample T-test because it is compared students’ score of two different groups to find out the relation and the difference among them. Table 4.4: The analysis of post-test score using independent sample T-test Independent sample T-test T Sig. (2 tailed) Eta squares Mean difference 95% Confidence Interval of the Difference Lower Upper Post Test Equal variances assumed Equal variances not assumed 2.150 2.150 .711 .06 5.509 5.509 .388 .393 10.631 10.626 As presented in the table above the result of students’ post-test score between control and experimental group shows that there is no significant difference between them. The result shows that the difference with 95% of CI = .388 to 10.626 with (p value=.711) higher than .05 (t=2.150) and the effect size of this comparison (eta square = .07) shows that the intervention is small. Therefore, it cannot simply conclude that fairy tales maze is failed to improve students’ comprehension on reading narrative text, because it can be seen from the analysis of the score between pre-test and post-test there is significant improvement on students’ score. However, fairy tales maze was not better than conventional material on improving students’ comprehension or in other word fairy tales maze is ineffective for teaching reading comprehension. The paired sample analysis of students’ score on pre and post test score shows that there is significant difference. The Mean value of this comparison is 43,78 on pre-test and 49,02 on pos-test. In addition, the Mean difference is -5,231 with CI 95% = (-8,208 to -2,254) and SD = 12,014, with p value = .001 (sig 2 tailed). The p value is less than .05, it indicates that there is significant difference on students’ score on pre-test and post test. On the implementation of this experiment, the researcher conducted five times meeting for the experimental group with three times treatment applied. Three times implementation of fairy tales maze for teaching reading comprehension through narrative text for eighth grade students is already exact times to conduct this study. On the first meeting, 60 minutes was taken to conduct pre-test and the 20 minutes remainder the researcher use this time to give brief introduction to the students about narrative, reading comprehension and fairy tales maze. On the second meeting the researcher use it for two times treatment with two different text. The first fairy tales maze is about “Goldilocks and the Three bears” the second text is “The frog prince”. On the third meeting the researcher use fairy tales maze “the three pigs”. At the last meeting the researcher conducted post-test for the experimental group. According to the analysis, the most students’ error since pre-test to the post test is on the comprehension question. Based on the result on pre-test, post-test and also during the teaching learning process researcher take some inferences that make this experiment shows that fairy tales maze was ineffective for teaching reading comprehension. Some reasons that make fairy tales maze is ineffective for teaching reading comprehension to the eighth grade students of SMPN 1 Tarik because, first, as stated at the previous chapter that for reading comprehension students’ or readers have to be able to connect their background knowledge (experience) and their present knowledge when reading. The subject in SMPN 1 Tarik had minimum background of knowledge related with the text they read. Some of them did not know about the fairy tales given by the teacher. Secondly, in reading comprehension readers must have good vocabulary knowledge. According to Anderson & Frebody (1993) on Scott (2009) stated that vocabulary knowledge and reading comprehension are strongly related. Consequently, it is impossible to understand a text well if readers have low vocabulary knowledge. In this study the subjects have minimum vocabulary knowledge, so it is hard to make them guest word correctly and comprehend the text well. Next, in the third reason why fairy tales was ineffective for teaching reading comprehension to the eighth grade students is because it was failed to attract the students’ attention to read. Some students getting confuse with the story because it was their first time to read that fairy tales story. Actually, as stated at the review of literature that one of the way to have good comprehension on the text is readers have to be able to predict the story by looking at the title. In this study because of the minimum vocabulary knowledge some students’ failed to understand even the title. The last, because of the minimum vocabulary knowledge also some students’ get confuse when they have to chose one correct word to complete the maze to get full story. As a conclusion, Fairy tales maze is ineffective for teaching reading comprehension to the eighth grade students of SMPN 1 Tarik. CONCLUSION According to the result of this study it can be concluded that there is no significant differences on the students’ reading comprehension between those who were taught using fairy tales maze (experimental group) and those who are taught without using fairy tales maze (control group). The inferences can be drawn that there is no significant differences because the finding of the study showed that the score of the control group (46,30) and experimental group (51,81) were nearly the same. Eventhough it is clearly seen that there is interval between experimental and control group, but it does not mean that there is significant differences between those two groups. According to the Independent sample T-test analysis on SPSS the mean value of control group’s score is 46,30 with SD =9.533. However, the mean value of the experimental group is 51,81 with SD = 10,702, and the p value of this analysis is 0,711. The p value was not less than 0.05 or higher than 0.05 means that there is no significant difference between these two groups. As a consequent, the finding of this study said that fairy tales maze was ineffective for teaching reading comprehension through narrative to the eighth grade students’ of junior high school in SMPN 1 Tarik. In addition, according to the analysis the alternative hypothesis (Ha) which stated that there is significant difference on students’ reading comprehension of narrative text between students’ who are taught by using fairy tales maze and those who are taught without using Fairy tales maze is rejected. However, the Null hypothesis (Ho) is accepted. It means that students’ comprehension was not increase eventhough the teacher used fairy tales maze for teaching them reading. In other word fairy tales maze was not better than the conventional material. There are some reasons that make eighth grade students did not comprehend the text well eventhough the teacher used fairy tales maze rather than common text or material. the first reason why students’ were failed on comprehending the text well is students were unable to use their background of knowledge to help them understand the information of the text because some of the text was new for them, it means that they did not had background of knowledge related with the fairy tale maze they read. Then, some of the students was getting confuse when they had to fill the blank with correct word choice because some of the students was lack of vocabulary knowledge. When students did not have background of knowledge related to the fairy tales and they also lack of vocabulary knowledge they will find difficulties to get information from the text. In conclusion, it is clear that fairy tales maze was ineffective for teaching reading comprehension to the eighth grade students. SUGGESTION In this part, the researcher would like to states some suggestions related with this study which might give contribution for the next researcher to conduct better research and also some beneficial suggestion for the reader. The researcher suggest for the reader also teacher that might use fairy tales maze for teaching reading the fairy tales maze that they use for students must be familiar to the students, because unfamiliar fairy tales story will unable to help students to connect their background of knowledge while they are reading. Besides, teacher also should pay attention on students’ ability for its consideration when choose the text that teacher going to use. The fairy tales story that use by the teacher for teaching material must be equal with the students’ grade and ability. However, to make a fairy tales maze, the maze or the distracter make by the teacher should be equal with the students’ vocabulary knowledge. Because, most students will find it difficult and hard to understand the text well when the maze is make in every seventh word after the first sentence. Since the finding of this study said that fairy tales maze is ineffective for teaching reading comprehension to the eighth grade students’ the next researcher might conduct the same research to the different subject with some changes on the maze (text) and the measurement instrument. The next researcher might give additional time for the test part, or reduce the number of the test item. In addition, this fairy tales maze can also be use for teaching learning process as the combination of drilling technique. REFERENCES Butler ,S. et al.(2010). A Review of the Current Research on Comprehension Instruction. National Reading Technical Assistance Center, RMC Research Corporation.( http://www.ed.gov/programs/readingfirst/support/index.html) last retrieved October 8th,2013. Departemen Pendidikan Nasional. (2006). Standar Kompetensi Mata Pelajaran Bahasa Inggris Sekolah Menengah Pertama dan Madrasah Tsanawiyah. Jakarta: Departemen Pendidikan Nasional. Finnochiaro, Marry. 1974. English as a Second Language from Theory to Practice. New York: Regent Publishing Company Ltd. Iwai, Y. (2007). Developing ESL/EFL Learners' Reading Comprehension of Expository Texts. Internet TESL, XIII, no 7. Milone, M. (2008). CORE READING MAZE COMPREHENSION TEST. NSW Department of Education Training (2010). Teaching comprehension strategies- Focus on reading. State of New South Wales, NEALS (online database material, last retrieved: 27 oktober 2013) Pallant, J. (2010). SPSS SURVIVAL MANUAL a step by step guide to data analysis using SPSS 4th edition (4th Edition ed.). New York: Allen & Unwin Book publisher, Australia. Rice, M.(2009) Reading Comprehension Skills and Strategies. Teaching Comprehension Strategies by NSW Department and Education Training 2010. State of New South Wales. Scott, S. E. (2009). Knowledge for teaching reading comprehension: Mapping the terrain. Dissertation, University of Michigan, Michigan.